Muntingia Calabura L. Leaves Extract Effect Towards Increment Of Nitric Oxide In Rattus Norvegicus - Ivander, Gian; Isbandiati, Endang; Jong, F.X. Himawan H. (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Hypertension is one of the leading health problem in Indonesia. One of the pathophysiology of hypertension is abnormality in nitric oxide production and transport. On the other side, Muntingia calabura L. is a plant that widely distributed in Indonesian and believed to possessed antinociceptive, antioxidant, antihypertension, and antimicrobial effect. Leaves of Muntingia calabura L. comprise of high phenolic compounds which is thought to increase nitric oxide production through the modulation of NOS and ROS inhibition. Aim: To analyze the effect of extract of Muntingia calabura L. leaves toward increment of nitric oxide in Rattus norvegicus. Method: This research is an in vivo experimental study with post-test only control group design, using nitric oxide strips test as measuring instrument. Sample of this experiment is forty Rattus norvegicus divided in five group which is negative control, positive control, treatment 1, treatment 2, and treatment 3. Extract of Muntingia calabura L. leaves with concentration 50, 100, 200 mg/mL given everyday on treatment group and measured every two days until six measurement is acquired. Result: There is increment of NO through administration extract of Muntingia calabura L. leaves in Rattus norvegicus. Conclusion: Highest increment of NO is obtained through administration of Muntingia calabura L. leaves extract at 200 mg/mL concentration.